Investigating Content and Language Integrated Learning Insights from Swedish High Schools - Sylvén, Liss Kerstin (Bilingual Education & Bilingualism, 2019)
This book provides a rich and unique longitudinal account of content and language integrated learning (CLIL). The chapters report on the findings from a large-scale, three-year research project undertaken at senior high school level in Sweden. The ecological perspective, with quantitative and qualitative methods, gives voice to both learners and teachers, as well as being an excellent critical example of how such longitudinal research might be carried out. Through emic and etic approaches, the book provides insights into language learning outcomes, both with regard to the target language English and the majority language Swedish; learner motivation among CLIL and non-CLIL students; effects of extramural exposure to English; issues in relation to assessment in CLIL and much more. As a whole, the book offers an unprecedented overview of learner outcomes and detailed insights into the comparison of CLIL and non-CLIL education. While it is embedded in the Swedish context, the nature of this study means that it has strong implications on an international basis